Analysis of infections caused by carbapenemase-producing gram-negative bacteria in a hospital in the Campos Gerais region (Research, Society and Development, 2021)
Objective: To determine the profile and prevalence of hospital infections caused by carbapenem-resistant Gram-negative bacteria related to healthcare. Methodology: This retrospective cross-sectional descriptive study (Yin, 2015) analyzed the profile of infections in a single public hospital by collecting data from electronic medical records. The collection included demographic data and infection-related clinical and laboratory findings. Results: We analyzed 193 acquisitions of Gram negative bacteria, 25 of which were by carbapenem-resistant microorganisms. Of these, the most common species detected was Klebsiella pneumoniae (56%, 14/25).  As for infections, the predominant hospital sector was the intensive care unit (56%, 14/25), mostly related to ventilator-associated pneumonia (40%, 10/25) and in patients submitted to some invasive procedure (72%, 18/25). About 50% of the patients had some adjacent health condition. Antimicrobial treatment prior to diagnosis was identified in 72% (19/25) of patients, with a predominance of betalactams (85.7%, 12/19) and after diagnosis, the majority used monotherapy (72%, 19/25). The impact of the infection was that 68% (17/25) were admitted to the intensive care unit, 40% (10/25) died, and 60% (15/25) were discharged. Conclusion: The results are in agreement with current literature and highlight the importance of prevention in combating the spread of these microorganisms in hospital environments.